Activation of the Ki-ras protooncogene in spontaneously occurring and chemically induced lung tumors of the strain A mouse. - You, M (1989)
The strain A mouse has a high incidence of spontaneous lung tumors and is susceptible to lung tumor induction by chemical carcinogens. By utilizing transfection assay, Southern blot analysis, and DNA amplification techniques, we have detected an activated Ki-ras gene in the DNAs of both spontaneously occurring and chemically induced lung tumors of strain A mice. The point mutations in the spontaneous lung tumors were in both codon 12 (60%) and codon 61 (30%). In contrast, 100% of the mutations in the Ki-ras gene detected in methylnitrosourea-induced lung tumors and 93% of the mutations in the Ki-ras genes detected in benzo[a]pyrene-induced lung tumors were in codon 12, whereas 90% of the mutations in the Ki-ras genes detected in ethyl carbamate-induced lung tumors were in codon 61. The selectivity of mutations in the Ki-ras oncogene observed in chemically induced tumors, as compared to spontaneous tumors, suggests that these chemicals directly induce point mutations in the Ki-ras protooncogene. These data indicate that the strain A mouse lung tumor model is a very sensitive system to detect the ability of chemicals to activate the Ki-ras protooncogene in lung tissue.